2013
DOI: 10.1007/s11274-013-1414-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five molecular subtyping methods for differentiation of Salmonella Kentucky isolates in Tunisia

Abstract: Salmonellosis is one of the most common causes of food-borne infection worldwide. In the last decade, Salmonella enterica serovar Kentucky has shown an increase in different parts of the world with the concurrent emergence of multidrug-resistant isolates. These drug-resistant types spread from Africa and the Middle East to Europe and Asia. Although S. Kentucky serovar is of potential human relevance, there is currently no standardized fingerprinting method for it, in Tunisia. In the present study, a collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
2
13
0
7
Order By: Relevance
“…Similar results were reported by several researchers (Fendri, et al, 2013;Turki et al, 2014). Further, a range of typing methods had been explored for the sub typing of S. Typhi and S. Typhimurium and PFGE was the most efficient and undisputed typing tool for Salmonella (Foley et al, 2006;Fakhr et al, 2005;Tsen et al, 2002).…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…Similar results were reported by several researchers (Fendri, et al, 2013;Turki et al, 2014). Further, a range of typing methods had been explored for the sub typing of S. Typhi and S. Typhimurium and PFGE was the most efficient and undisputed typing tool for Salmonella (Foley et al, 2006;Fakhr et al, 2005;Tsen et al, 2002).…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…These results are in agreement with other workers who reported that PFGE is one of the most reli-able techniques for discriminating different serotypes of Salmonella (10,13,35,36).…”
Section: Discussionsupporting
confidence: 93%
“…Human isolates were obtained from the National Center for Enteropathogenic Bacteria at Pasteur Institute, Tunis, Tunisia. Isolation and identification were performed as described by Turki et al (2014). Serotyping was achieved at the National Center for Enteropathogenic Bacteria at Pasteur Institute, Tunis, Tunisia, on the basis of somatic O, phase 1 flagellar, and phase 2 flagellar antigen agglutination using commercial antisera (Bio-Rad, France) according to the White-Kauffman-Le Minor scheme of Popoff (2001).…”
Section: Methodsmentioning
confidence: 99%
“…The genomic DNAs of the Salmonella strains were extracted according to the method described by Turki et al (2014).…”
Section: Methodsmentioning
confidence: 99%